Oral health and functional capacity of centenarians - Sekundo, Caroline; Langowski, Eva; Kilian, Samuel; Frese, Cornelia (Scientific reports, 2020)
The number of very old individuals, namely centenarians, is growing fast. In dentistry, the increasing number of older adults retaining natural teeth present new challenges for preventive and restorative dental care. However, there is a considerable lack of knowledge on the oral health status and needs in this exceptional age group. The aim of this population-based study was to identify the prevalence of oral diseases, therapeutic needs and functional capacity (evaluating centenarians’ autonomy and their capabilities regarding treatment and oral hygiene) in centenarians. Subjects born before 1920 were recruited from population registries in South-Western Germany, providing information on dental health experiences, oral health behaviors and undergoing dental examination. 55 centenarians participated in the study (mean age ± SD = 101.2 ± 1.6, 83.6% females). Results were compared to epidemiological data on adults aged 75-100 years examined in the Fifth German Oral Health Study. Adherence to recommended dental behaviors and dental check-ups was lower in the centenarian population. Moreover, with the exception of a lower Root Caries Index, centenarians showed a higher caries experience, and presented with a mean DMFT of 25.2 ± 3.9, a DMFS of 111.0 ± 21.8, a root caries prevalence of 34.5% and a Restorative Index of 54.0%. Centenarians’ functional capacity was also considerably lower. Non-existent or greatly reduced treatment capabilities and oral hygiene capabilities were registered in 63.7% and 43.6% of cases, respectively. Centenarians with a lower educational level (p = 0.018), in a care facility (p = 0.045) or in need of nursing care (p = 0.001) were more likely to have a low functional capacity. 98.2% of centenarians received help in their daily activities but only 12.7% in their oral hygiene. In conclusion, although most still have natural teeth, a decline of oral health can be perceived. As compliance with recommended behaviors is limited and most centenarians can no longer undergo dental treatment, the lack of assistance in daily oral health care is problematic.
Gesehen am 28.01.2021